Analysis of the Three-Dimensional Accelerating Flow in A Mixed Turbine Rotor - Chelabi, Mohammed Amine; Basova, Yevheniia; Hamidou, M. K.; Dobrotvorskiy, Sergiy (Sumy State University, 2021)
An investigation on new rotor blade designs conceived to produce higher exit relative kinetic energy of a mixed flow turbine is undertaken. Accelerating the flow through the rotor in a relative frame of reference improves energy transfer to the shaft, which is only produced in a rotating rotor. A three-dimensional converging rotor channel might respond to the analysis requirements in the subsonic flow regimes. Effectively, the machine experiences a 3.71 % and 3.67 % increase in work output and efficiency, respectively, representing this study’s primary intent. This has been accomplished by varying the shroud profile to a lesser eye tip diameter, then the hub profile to a larger eye root diameter. At last, both shroud and hub profiles are varied. It appears possible to enhance the performance of the rotor in terms of optimum work done and efficiency by devising suitable blade geometry designs. ANSYS CFX 15 is the code of all simulation works.
Keywords: blade; vane-to-vane plane; hub; shroud; meridional plane